ANALISIS ANTRIAN PENGUNJUNG DAN KINERJA SISTEM DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Astrelita, Fahra Pracendi; Sugito, Sugito; Wuryandari, Triastuti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Department of Population and Civil Registration (Dispendukcapil) has the duty of assistance in the field of population and civil registration. Civil registration services such as services related to birth, death, marriage, and divorce. As a service provider, Dispendukcapil of Semarang has the motto